IN VITRO ANTIMICROBIAL AND ANTIOXIDANT PROFILE OF STREPTOMYCES SP. ISOLATED FROM COROMANDEL COAST REGION, INDIA - PANNEERSELVAM KIRUTHIKA; S DURAIRAJU NISSHANTHINI; JAYARAMAN ANGAYARKANNI (International Journal of Pharma and Bio Sciences, 2013)
Marine actinomycetes were isolated from the sediments collected from Coromandel Coast region, India. The strain designated as BI244 was found to be an efficient pigment (dark brown-black) producer and has been selected for further studies. The organism was identified as Streptomyces sp. based on morphological, biochemical and physiological characterization. Phylogenetic tree constructed for 16s rRNA gene sequence by weighted-neighbor joining method showed 98% similarity to Streptomyces sp. NBRC 13020. The pigment extracted with methanol showed broad spectrum antimicrobial activity towards gram positive and gram negative bacteria and yeast. The extract also possessed DPPH free radical scavenging activity and the IC50 value was found to be 3.5mg/mL. The results of antimicrobial and antioxidant activity produced by the pigment extract clearly indicated that the marine environment is a untrapped source for isolation of bioactive compounds from actinomycetes.